2010
DOI: 10.3390/d2111181
|View full text |Cite
|
Sign up to set email alerts
|

The CC-Bio Project: Studying the Effects of Climate Change on Quebec Biodiversity

Abstract: Anticipating the effects of climate change on biodiversity is now critical for managing wild species and ecosystems. Climate change is a global driver and thus affects biodiversity globally. However, land-use planners and natural resource managers need regional or even local predictions. This provides scientists with formidable challenges given the poor documentation of biodiversity and its complex relationships with climate. We are approaching this problem in Quebec, Canada, through the CC-Bio Project (http:/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 71 publications
1
50
0
Order By: Relevance
“…As mentioned by several authors, we need to go toward a common, modern and broader vision of biodiversity conservation. Scientific community, together with decision-makers in agencies, governments and non-governmental organizations, should thus carefully reconsider conservation priorities and, possibly, in order to avoid duplicating efforts (Mace, 2000), establish close partnerships (Berteaux et al, 2010;Maury et al, 2013) to develop successful conservation strategies for biodiversity management (Heller and Zavaleta, 2009). Because of the complexity of the topic and the unpredictability brought by climate change, there is no single definitive praxis to effective conservation, but rather an interdisciplinary approach.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As mentioned by several authors, we need to go toward a common, modern and broader vision of biodiversity conservation. Scientific community, together with decision-makers in agencies, governments and non-governmental organizations, should thus carefully reconsider conservation priorities and, possibly, in order to avoid duplicating efforts (Mace, 2000), establish close partnerships (Berteaux et al, 2010;Maury et al, 2013) to develop successful conservation strategies for biodiversity management (Heller and Zavaleta, 2009). Because of the complexity of the topic and the unpredictability brought by climate change, there is no single definitive praxis to effective conservation, but rather an interdisciplinary approach.…”
Section: Resultsmentioning
confidence: 98%
“…The combined effect of these anthropogenic pressures may have already started a critical transition toward a tipping point (Barnosky et al, 2012). In particular, climate is modifying rapidly forcing biodiversity to adapt either through the change of habitat and life cycles or the development of new physical traits (Berteaux et al, 2010). For instance, rising temperatures can lead to potential biodiversity increases in northern regions (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally suggested that high temperatures (either in a greenhouse interval or during interglacials within icehouse intervals) are associated with high diversity (Cecca, 2002) and that high temperature is crucial for the establishment of new species (Berteaux et al, 2010). At global scales, the late Viséan was a time a high marine biodiversity (e.g.…”
Section: Origin Of Biodiversitymentioning
confidence: 99%
“…Birds are likely to react directly to climate change events such as repeated periods of rain, frost, and heat, and indirectly to changes in the environment that influence features such as food availability, habitat structure, and relationships among organisms. Because of the milder climate expected throughout most of the province of Québec in coming decades, certain bird species' ranges are predicted to expand northward (Berteaux et al 2010). If temperature is one of the main drivers of bird species richness, we could expect more bird species in the southern portion of the boreal forest.…”
Section: Introductionmentioning
confidence: 99%